KEMAMPUAN GURU MI YANG BERSERTIFIKAT PENDIDIK DALAM MENYUSUN RENCANA PEMBELAJARAN (Kasus Kota Pekalongan) - Imam Suraji; Wamugi; Aris Nurkhamidi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2013)
This study aimed to investigate the capability of certified teachers of Islamic elementary school located in Pekalongan City in preparing lesson plan. Fourteen informants – consist of 6 government teachers and 8 non-government teachers – were investigated. The data were taken from the lesson plan documents prepared by them and then followed up with an interview. The results showed that: (1) there are many teachers who have not been able to develop their own learning devices, and (2) there are still very much in error that occurred in the lesson plan prepared by them. There are several constraints faced by them. They are: (1) their knowledge is still lack, their innovation and creativity were not maximized; (2) the pattern of development for them had not touched their academic aspect; (3) the orientation of the supervisions which only leaded to the administrative aspects; and (4) their independence lack in preparing learning device, which is part of the curriculum.